STUDENTS’ COMPETENCE IN PREDICTING PICTURE ON READING TEXT AT SENIOR HIGH SCHOOL - Rahmah Rahmah (BAHAS, 2016)
The objective of the present study is to find out the competence of predicting information through picture by students of SMA Utama Medan. 1 Classes of 5 was taken as a sample of this research. The data of this study were obtained from the students’ score of reading test. Based on the result of data analysis, it was found that the competence in predicting information through picture is very good.From 32 sample students, there were 20 students (62.5%) got very good score or can predict more than 5 details of information from the text, 10 students (31.25%) got good score or can predict less than 5 details of information from the text and only 2 students (6.25%) got bad score or predict less than 2 information. As well as their reading comprehension of the text with mean score 84.37 which is higher than the Minimal Completeness Criteria (KKM) of reading applied by SMA Utama. It can be concluded that the used of pictures as the tools in teaching reading has positive impacts in teaching reading to students, especially in getting their attention, activating their background knowledge and motivates them to read and figure out the content of the text.   Keywords: Students’ competence, Predicting, Reading text.